2010
DOI: 10.1007/s00038-010-0161-4
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of sexually transmitted infections among reproductive age women in St. Petersburg, Estonia and Finland

Abstract: Risky behaviour predicts STIs, but does not explain the varying rates of STIs between areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
2
2
1
Order By: Relevance
“…Similarly, other studies have shown sexually transmitted diseases to be higher in women who had their first sexual intercourse aged under 18 years. 21 We did not find that syphilis was associated with our monetary indicator of poverty; nor was it associated with household poverty according to the modified basic necessities index. This observation is different from a study in a Brazilian population which found congenital syphilis to be associated with a monthly per capita income of below US$ 30.…”
Section: Discussioncontrasting
confidence: 60%
“…Similarly, other studies have shown sexually transmitted diseases to be higher in women who had their first sexual intercourse aged under 18 years. 21 We did not find that syphilis was associated with our monetary indicator of poverty; nor was it associated with household poverty according to the modified basic necessities index. This observation is different from a study in a Brazilian population which found congenital syphilis to be associated with a monthly per capita income of below US$ 30.…”
Section: Discussioncontrasting
confidence: 60%
“…The odds of self-reported syndromes of STIs among reproductive age women having educational level of higher education and above were higher than women of a lower Education level. This is consistent with studies in Estonia, and Finland [ 34 ]. This might be due to the fact educated women are more likely to report their reproductive health status than uneducated women.…”
Section: Discussionsupporting
confidence: 93%
“…Self-reporting syndromes of STIs was influenced by different factors such as; age, marital status, educational status, ever had termination of pregnancy, and risky sexual behaviors are associated with self-reported STIs. This is similar to the findings in Swaziland, Nepal, Uganda, India, and Petersburg Estonia [24,28,29,30,31,34].…”
Section: Discussionsupporting
confidence: 90%
“…Each participant was asked to report his or her age of first sexual intercourse. Consensus on what age is considered to represent an early debut has not been reached in the literature, with various studies using different ages as the cut-off, such as 14 years old or younger [71], 16 years old or younger [72][73], or even 17/18 years old or younger [74]. Depending on the age used, the percentage of early initiators range from 17% [72] to 44% [73].…”
Section: Risky Sexual Behavior (Wave 8-wave 10)mentioning
confidence: 99%